2003
DOI: 10.1021/jp034379y
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Spectra of Antimony and Bismuth Hydrides in Solid Matrixes

Abstract: Laser-ablated Sb and Bi atoms react with hydrogen during condensation in excess hydrogen, neon, and argon to form the SbH and BiH diatomic molecules. In addition the new Group 15 MH2 dihydride radicals and the MH3 trihydrides are observed for Sb and Bi metals. Although BiH3 is of limited stability in the gas phase, BiH3 is formed by further H atom reactions with BiH2 in solid hydrogen and neon. No evidence is found for the thermochemically unstable BiH5 molecule.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
40
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 42 publications
3
40
0
Order By: Relevance
“…[8] Our TlH 3 band absorbance is much less intense than that observed for InH 3 , which in turn is expected to be much less than that observed for GaH 3 and AlH 3 . [16,17,24,25] Evaporation of the H 2 (D 2 ) matrix gave no evidence of broad absorption bands in the 1500-700 cm À1 region that might be due to solid thallium hydride. Our failure to observe (TlH 3 ) n at low temperature is due to the inherent instability of the Tl III hydride, which is also manifested in a low yield of TlH 3 .…”
Section: Methodsmentioning
confidence: 95%
“…[8] Our TlH 3 band absorbance is much less intense than that observed for InH 3 , which in turn is expected to be much less than that observed for GaH 3 and AlH 3 . [16,17,24,25] Evaporation of the H 2 (D 2 ) matrix gave no evidence of broad absorption bands in the 1500-700 cm À1 region that might be due to solid thallium hydride. Our failure to observe (TlH 3 ) n at low temperature is due to the inherent instability of the Tl III hydride, which is also manifested in a low yield of TlH 3 .…”
Section: Methodsmentioning
confidence: 95%
“…Ga 2 H 4 has been sighted in matrix-isolation experiments. [44] Derivatives such as Ga 2 Cl 4 or the hydride Ga 2 Cl 3 H have been synthesized and characterized by single-crystal X-ray diffraction. [45,46] Like Ga 2 Cl 4 , Ga 2 H 4 seems to prefer a C 3v symmetric structure, which can be described roughly as an ion pair Ga + [GaH 4 ] À .…”
mentioning
confidence: 99%
“…[4] Bi II radicals were suggested to be the active species based on reactivity studies with trapping reagents and substoichiometric amounts of radical inhibitors.D irect IR spectroscopic evidence for the existence of the short-lived, in situ generated Bi II radicals H 2 BiC and HMeBiC has been obtained using matrix-isolation techniques (Scheme 1b). [5] Following these initial studies on transient Bi II radicals, the first persistent bismuth-centered radical was reported by Ishida, Iwamoto,a nd co-workers.I tw as shown that these species can indeed be handled in solution at room temperature under an inert atmosphere when stabilized by ab ulky supporting ligand. [6] Ther adical species 1 exists in at emperature-dependent equilibrium with its dimer, dibismuthane (1) 2 (Scheme 2a).…”
mentioning
confidence: 97%
“…[9] Lowtemperature matrix-isolation techniques enabled the IR spectroscopic characterization of monomeric BiH (Scheme 3b). [5] Thei solation of the first stable mononuclear Bi I species as adeep blue crystalline material was achieved only recently by Dostµl et al (Scheme 3c). [10] Thea ryl diimine ligand used in this study stabilizes the Bi I center both sterically (shielding of ap -a nd an s-type Bi-centered lone pair) and electronically (dative interactions of the imine moieties with an empty,B i-centered p-type orbital).…”
mentioning
confidence: 99%
See 1 more Smart Citation